Purificação, caracterização e atividades biológicas de uma lectina da esponja marinha Aplysina fulva (AFL) - Gomes Filho, Sandro Mascena (2014)
A new lectin was purified and characterized from marine sponge Aplysina fulva (AFL). The crude extract was obtained with Tris HCl 0.1 M pH 7.4 containing NaCl 0.15 M buffer. Haemagglutinating activity detection and soluble protein measurement were performed with the crude extract and after each purification step. Isolation of AFL was performed by affinity chromatography in Sepharose CL 4B column, and the retained peak was applied in a DEAE Sephacel ion exchange chromatography column. Analysis of DEAE Sephacel retained peak on polyacrylamide gel electrophoresis (SDS-PAGE) showed the presence of a single band with approximately 27.5 kDa. Under non-denaturating conditions it shows the presence of a single 57 kDa band. The novel lectin showed large amount of hydrophobic amino acids, high temperatures resistance and better hemagglutination activity in the range of neutral to alkaline pHs. AFL was able to inhibit the growth of strains of P. aeruginosa, C. albicans and C. tropicalis. The lectin did not show toxic effects on cells of breast cancer, but had agglutination effect on Leishmania brasiliensis promastigotes by recognizing galactose residues on its surface.